O Fetiche do Capital Intelectual: A ideologia do Conhecimento e da Adaptação no Contexto da Reestruturação Produtiva do Capital - Alves, Giovanni Antonio Pinto [UNESP]; Batista, Roberto Leme (My University, 2010)
This article presents a discussion about the fetishism of the intellectual capital, analysing the ideology of knowledge and the need of adaptation of the worker in connection with the restructuring of capital in recent decades. We analyze the emergence of this ideology - through the concepts of knowledge society, information society, intellectual capital, among others - in some authors of the area human resource management, following it presents the critique of this notion based on the analysis of some authors of critical social thought. Finally we position ourselves in order to assert that this is a new version of fetishism in the time of globalization of the capital.

Neste artigo apresentamos uma discussão acerca do fetichismo do capital intelectual, ao analisar a ideologia do conhecimento e a exigência de adaptação do trabalhador no contexto da reestruturação do capital nas últimas décadas. Para tanto, analisamos a emergência dessa ideologia – através dos conceitos de sociedade do conhecimento, sociedade da informação, capital intelectual, entre outros – em alguns autores da área de gestão de recursos humanos, na sequência apresenta a crítica desse ideário a partir da análise de alguns autores do pensamento social crítico. Finalmente nos posicionamos no sentido de afirmar que se trata de uma nova versão do fetichismo na era da mundialização do capital.
The fetish of intellectual capital: the ideology of knowledge and adaptation in the context of restructuring process of capital
Keywords: Trabalho; Educação; Globalização